ANALISIS POSISI BERSAING UNTUK MENENTUKAN STRATEGI PEMASARAN UMKM DI KOTA MALANG - Rahayu, Yayuk Sri (IQTISHODUNA, 2012)
This research aimed to find competitive position and to determine marketing strategic based on competitive position of producer â€œkripik tempeâ€ atÂ  Sanan Kota Malang. Number of responden are thirty companies or 11% of population and the sampling method is purposive sampling. The variables consist of sales, production, price, equity, period of business, and employee. Cluster analysis was used to answer the aim of this research. The result shows competitive position of the produser â€œkripik tempeâ€ shared in four cluster are: first cluster named market leader consist of one company, second cluster named market nicher consist of thirteen companies, third cluster named market challenger consist of six companies, and the last cluster named market follower consist ofÂ  ten companies. Based on this cluster, the company that produce â€œkripik tempeâ€ can determine dan implement marketing strategic according each competitive position.